Environmental Pollutants and Neurodevelopment: Review of Benefits From Closure of a Coal-Burning Power Plant in Tongliang, China - Vrinda Kalia MPH; Frederica Perera PhD, DrPH; Deliang Tang MD, DrPH (SAGE Publishing, 2017)
Background . Understanding preventable causes of neurodevelopmental disorders is a public health priority. Polycyclic aromatic hydrocarbons (PAH) from combustion of fossil fuel, lead, and mercury are among known neurodevelopmental toxicants. Method . For the first time, we comprehensively review the findings from a study by the Columbia Center for Children's Environmental Health and Chinese partners that followed 2 groups of mother-child pairs, one from 2002 and another from 2005, in Tongliang County, China. Pregnant mothers in the 2 cohorts experienced different exposure to PAH because a local coal-burning power plant was shut down in 2004. Investigators assessed change in prenatal PAH exposure, measured using a biomarker (benzo[a]pyrene [BaP]-DNA adducts in cord blood). Developmental quotients were measured using the Gesell Developmental Scales at age 2 and IQ was assessed using the Wechsler Intelligence Scale for Children at age 5. Biologic markers of preclinical response were measured in cord blood: methylation status of long interspersed nuclear elements ( LINE1 ), an indicator of genomic stability, and brain-derived neurotrophic factor (BDNF), a neuronal growth promoter. Analyses accounted for co-exposure to lead and mercury. Results . BaP-DNA adducts were significantly inversely associated with Gesell Developmental Scales scores in the first cohort but not in the second cohort; and levels of BDNF and LINE1 methylation were higher in the second cohort. Conclusion . In this study, reduced exposure to PAH was associated with beneficial effects on neurodevelopment as well as molecular changes related to improved brain development and health. These benefits should encourage further efforts to limit exposure to these toxic pollutants.